PENGARUH TINGKAT STRES KERJA DAN KONDISI FISIK PEKERJAANTERHADAP PRESTASI KERJA PEGAWAI NEGERI SIPIL DI LINGKUNGAN SEKRETARIAT DAERAH KABUPATEN BIREUEN YANG DIMEDIASI OLEH KEPUASAN KERJA - Denny Sumantri Mangkuwinata (Ekonis: Jurnal Ekonomi dan Bisnis, 2017)
Abstract: This study examines the influence of the level of work stress and physical conditions of work on work performance are mediated by job satisfaction. samples in this study were 176 people civil Bireuen District Secretariat. The analysis tool used is a hierarchical regression techniques. The results showed that the level of work stress and physical conditions of employment on job satisfaction. The level of work stress have a positive effect on work performance of employees, while the physical condition of employment does not affect the work performance of employees. Further more, job satisfaction act as a mediating variable between the correlation job stress and job performance of employees. Keywords : Job Stress levels, Physical Condition Employment, Job Satisfaction, Job Performance